PENGEMBANGAN MODUL AJAR BERBASIS MASALAH DALAM IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI TERHADAP PENINGKATAN KEMAMPUAN NALAR KRITIS SISWA - Reka Diana Permata Sari; Riswanto; Eko Prihandono (JURNAL FIRNAS, 2025)
Abstract: The purpose of this research is to determine the feasibility of problem-based teaching modules, to understand the application of problem based teaching modules in differentiated learning, and to measure the improvement in students' critical thinking skills. This research is motivated by several problem factors identified from the results of questionnaire distribution and interviews, namely the still low critical thinking skills, the absence of differentiated learning implementation, and the use of the discovery learning model with the lecture method. The research method used is R&D (Research and Development) with the ADDIE development model, which includes five development stages: analyze, design, development, implementation, and evaluation. Research data were collected using expert validation questionnaires for teaching modules, user response questionnaires for teachers and students, test item validation sheets, and test items. The feasibility of the problem-based teaching module on alternative energy materials is overall categorized as very feasible with a percentage of 91.66%, which consists of expert validation of the teaching module. The implementation of problem-based teaching modules in differentiated learning, as seen from the results obtained through initial assessments or diagnostic assessments, shows three groups of learning styles: the visual group with 9 students achieving a percentage score of 85.55%, the auditory group with 8 students achieving a percentage score of 85.75%, and the kinesthetic group with 8 students achieving a percentage score of 87.25%. Based on the user response questionnaire results from each group—visual, auditory, and kinesthetic—the implementation of differentiated learning was effective and very well conducted in the learning activities. The average percentage scores from both teachers and students were very good, at 86.4% and 86.13%, respectively. The use of problem-based teaching modules can enhance students' critical thinking abilities. This is evidenced by a significant improvement in students' critical thinking test scores, with an N-gain score of 0.81 in the high category.